Analisis Kebijakan Pencegahan Penggunaan Lahan Pertanian ke Non Pertanian di Kabupaten Bungo Provinsi Jambi - Dolly, Fajar Ifan (Sawala : Jurnal Administrasi Negara, 2018)
This study aims to look at the development of agricultural land use in Bungo District for the use of other businesses such as plantations, mining, and other commercial buildings as well as analyze policies in the use of agricultural land to non-agriculture. This research applies qualitative methodology in descriptive analysis. The results of the research are formulated as alternative policies, namely the formulation of policy revisions or renewal of Regional Regulation Number 13 concerning the 2013-2023 Regency Spatial Planning and Regency of Bungo. Next steps are determined from the results of the recommendations as follows: (i) Immediately formulate and formulate policies by inviting all stakeholders to prevent the practice of transferring agricultural land to other uses; (ii) This rule can be implemented by involving various roles from agricultural groups in the village on an ongoing basis and inviting cooperation with the local village government; (iii) When a business actor who wants to use agricultural land for other purposes must go through environmental analysis and studies and can only be used by the community that has the original identity of the village in question. The Bungo District Government needs to do (i) preventive prevention by inviting all stakeholders in the village government (ii) validation of regulations related to the use of productive agricultural land use in the 2013-2023 RTRW Perda.